PENERAPAN MODEL PROJECT BASED LEARNING, VISUAL, AUDITORI, KINESTETIK, DAN COURSE REVIEW HORAY UNTUK MENINGKATKAN AKTIVITAS DAN BERPIKIR KRITIS SISWA PADA PELAJARAN MATEMATIKA DI SDN KUIN SELATAN 5 - Fatimatuz Zahra; Darmiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the low level of student activity, critical thinking skills, and learning outcomes in mathematics learning, specifically in the topic of calculating the area of plane figures. This issue arose due to monotonous learning methods, insufficient stimulation of critical thinking, and learning outcomes that had not met the Learning Objectives Achievement Criteria. To address these problems, a combination of Project-Based Learning, Visual, Auditory, Kinesthetic, and Course Review Horay models was applied. This research employed Classroom Action Research (CAR) with the subjects being 10 fifth-grade students at South Kuin Public Elementary School 5 Banjarmasin. The results showed that teacher activity achieved the “Very Good” category, student activity was “Very Active,” critical thinking skills were “Very Skilled,” and learning outcomes achieved classical mastery. Therefore, the combined learning models were proven effective in improving student activity, critical thinking skills, and learning outcomes in mathematics learning on calculating the area of plane figures